Application of React Learning Model to Increase Students' Physics Learning Activities and Achievements - Wulandari, Ratna Wahyu; Rochana, Siti (Islamic Journal of Integrated Science Education (IJISE), 2022)
This study was attempted to solve the problem of the problem using the aim of increasing the activities and learning achievement of physics students in class VIII D MTsN 7 Kediri using the REACT learning model. The type of research used is classroom action research using two cycles. Each cycle consists of planning, application of activities, observation, and reflection. The action given is the application of REACT learning model. The study was conducted at the MTsN 7 Kediri using class VIIID research subjects using a total of 37 students, all of whom were female students. The research instrument used was an observation sheet on the implementation of education, an observation sheet for student learning activities, and a test. Physics learning activities and achievements are said to be successful if the mastery of learning both has reached 75% of all students. The results of the study show that the application of REACT learning model can improve the activities and learning achievements of students in class VIIID MTsN 7 Kediri. Overall student learning activities face an increase in cycle I to cycle II as much as 14.92%. Students' physics learning achievement faces an increase in the time before the action to cycle I and cycle II which is as much as 10.46% and the class can be said to have completed learning.